Buchanania lanzan, Spreng-studies on Methods of Propagation and Estimation of Fruit Yield - Rai, Y. C. (Indian Forester, 1982)
B. lanzan (chiraunji. Piar. Achaar. Chaar) is an important species of Peninsular India, yielding valuable edible seeds used in condiments, but surprisingly, It has continued to be neglected in the matter of scientific studies. This paper gives certain new information on its population in U.P., its seed production capacity, seed size, characteristics of Chiraunji bearing soils, proper sowing period, mode of sowing, composition of its seeds, and certain properties of its gum, along with the identification of an insect damaging its stems, with a view to interest foresters all over the country to conduct further research work on this economically valuable species with a view to expand the area under its cultivation.